The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/f11030346
|View full text |Cite
|
Sign up to set email alerts
|

Combining Climate Change Mitigation Scenarios with Current Forest Owner Behavior: A Scenario Study from a Region in Southern Sweden

Abstract: This study investigates the need for change of current forest management approaches in a southern Swedish region within the context of future climate change mitigation through empirically derived projections, rather than forest management according to silvicultural guidelines. Scenarios indicate that climate change mitigation will increase global wood demand. This might call for adjustments of well-established management approaches. This study investigates to what extent increasing wood demands in three climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…As interviewees opted for very different adaptive forest management orientations, ranging from business-as-usual to transformative strategies, we decided to build a typology of adaptation behaviors. This typology is based on influential structural variables and logics of action that are commonly found in forest owners' typologies (Deuffic et al 2018;Ficko et al 2019;Van Herzele and Van Gossum 2008;Weiss et al 2019) and attitudes towards climate change (André et al 2017;Blennow et al 2012;Lodin et al 2020;Van Gameren and Zaccai 2015):…”
Section: Tab 1 Case Study Areas and Interviewees' Characteristicsmentioning
confidence: 99%
“…As interviewees opted for very different adaptive forest management orientations, ranging from business-as-usual to transformative strategies, we decided to build a typology of adaptation behaviors. This typology is based on influential structural variables and logics of action that are commonly found in forest owners' typologies (Deuffic et al 2018;Ficko et al 2019;Van Herzele and Van Gossum 2008;Weiss et al 2019) and attitudes towards climate change (André et al 2017;Blennow et al 2012;Lodin et al 2020;Van Gameren and Zaccai 2015):…”
Section: Tab 1 Case Study Areas and Interviewees' Characteristicsmentioning
confidence: 99%
“…The need to understand decision-making in terms of climate-related risks in climatesensitive sectors such as forestry is widely recognized [15][16][17][18]. This includes the need for models that can simulate future adaptations under evolving climatic and socio-economic uncertainty by explicitly representing adaptation and non-rational behaviours that underpin decision making [11,19].…”
Section: The Need For Modelling Alternatives In the Forestry Sectormentioning
confidence: 99%
“…Simulation systems have been widely used to project the future provision of goods and services and analyze the effect of changing forest policies or even the impacts of climate change. Lodin et al [20] investigated the extent of increasing wood demands under defined climate change mitigation scenarios with different management intensities in Sweden using the Heureka Planwise DSS system. They showed that the achievement of traditional forest management objectives is truly limited to the projected climate change scenarios.…”
Section: Case Studies With Simulation and Scenario Analysismentioning
confidence: 99%